The role of abatement technologies for allocating free allowances - Clémence Christin; Jean-Philippe Nicolai; Jerome Pouyet (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2011)
The issue of how to allocate pollution permits is critical for the political sustainability of any cap-and-trade system. Under the objective of offsetting firms' losses resulting from the environmental regulation, we argue that the criteria for allocating free allowances must account for the type of abatement technology: industries that use process integrated technologies should receive some free allowances, whereas those using end-of-pipe abatement should not. In the long run, we analyze the interaction between the environmental policy and the evolution of the market structure. In particular, a reserve of pollution permits for new entrants may be justified when the industry uses a process integrated abatement technology.
Keywords: L13; Q53; Q58; 330; Cap-and-trade system; profit-neutral allocations; abatement technologies